2021
DOI: 10.1146/annurev-pharmtox-050120-105018
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic Drugs: Reducing Senescent Cell Viability to Extend Health Span

Abstract: Senescence is the consequence of a signaling mechanism activated in stressed cells to prevent proliferation of cells with damage. Senescent cells (Sncs) often develop a senescence-associated secretory phenotype to prompt immune clearance, which drives chronic sterile inflammation and plays a causal role in aging and age-related diseases. Sncs accumulate with age and at anatomical sites of disease. Thus, they are regarded as a logical therapeutic target. Senotherapeutics are a new class of drugs that selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
150
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(176 citation statements)
references
References 97 publications
(124 reference statements)
0
150
0
Order By: Relevance
“…Likewise, it will be interesting to consider whether interventions that extend lifespan or healthspan act by shifting the balance between digital states at the cellular level. As an example, senolytic therapy is clearly aimed at enhancing healthspan by cells in a particular state, not all cells in an aged tissue 56 . Aging is associated with changes in the population of immune cell infiltrates 51 , and caloric restriction can reverse those trends 50 .…”
Section: Digital Aging Versus Analog Agingmentioning
confidence: 99%
“…Likewise, it will be interesting to consider whether interventions that extend lifespan or healthspan act by shifting the balance between digital states at the cellular level. As an example, senolytic therapy is clearly aimed at enhancing healthspan by cells in a particular state, not all cells in an aged tissue 56 . Aging is associated with changes in the population of immune cell infiltrates 51 , and caloric restriction can reverse those trends 50 .…”
Section: Digital Aging Versus Analog Agingmentioning
confidence: 99%
“…Studies with mice showed that removal of senescent cells can prevent or delay tissue dysfunction [78]. Therefore, several senolytics are now tested in clinical trials for treating diverse conditions such as frailty and AD [77], and the administration of senolytics has also been suggested as a potential strategy for delaying progression of MS [79]. The therapeutic modulation of telomerase activity is another approach that is currently being pursued mainly in cancer trials [80].…”
Section: Discussionmentioning
confidence: 99%
“…The use of vitamin E and other antioxidants in MS patients is still unclear due to a lack of sufficiently powered studies [75]. Besides, senolytic drugs have been discussed to improve chronic diseases and functional deficits by enhancing immune-mediated clearance of senescent cells [76,77]. Studies with mice showed that removal of senescent cells can prevent or delay tissue dysfunction [78].…”
Section: Discussionmentioning
confidence: 99%
“…At first, senescence is initiated by the activation of p53/p21 CIP1 and p16 INK4a /Rb pathways by several stresses, such as DNA damage or reactive oxygen species (ROS) among others [ 9 ]. Downstream, the spreading of these signals is mediated by ATM, IKK/NF-κB, JAK/STAT, GATA4 and mTOR signal transducers, amplifying the senescence response [ 10 ].…”
Section: Measuring Cellular Senescence In Vivomentioning
confidence: 99%
“…Senotherapeutics are a new class of drugs that selectively kill senescent cells (senolytics) or suppress their SASP (senomorphics or senostatics) without killing the senescent cell [ 10 ]. Senescent cells mainly depend on the immune system to be cleared; thus, a dysfunctional immune system will lead to accumulation of senescent cells within tissues.…”
Section: Bcl-xl As a Senolyticmentioning
confidence: 99%